Capital structure determinants of Shariah and Non-Shariah companies at Bursa Malaysia - Hussain H.I., Abdul Hadi A.R, Rehan R., Zainudin Z., (Opción, 2019)
This paper attempts to investigate the effect of total assets, fixed assets, current assets, sales, return on equity and earning per share on the capital structure of Shariah and Non-Shariah listed companies at Bursa. The methodology is based upon static panel data analysis, namely Fixed Effect and Random Effect Models. The empirical results show that assets and sales are important in explaining firm’s capital structure in Shariah companies. In conclusion, any increase in the level of firm’s current asset is likely to be supported by short-term borrowings. As such, working capital management seems credible in explaining firm’s choice of financing.